2016
DOI: 10.1002/mdc3.12436
|View full text |Cite
|
Sign up to set email alerts
|

24/7 Live Stream Telemedicine Home Treatment Service for Parkinson's Disease Patients

Abstract: Background Treatment of advanced‐stage idiopathic Parkinson's disease (PD) is a demanding challenge, and in Germany, medication regimen adjustments are often made during inpatient stays. Admissions often follow an acute worsening of symptoms and functioning. In order to reduce long and expensive inpatient stays, and to provide more frequent consultations, a 24/7 live stream telemedicine home treatment service was established. Methods A pilot study was conducted in which laptops were distributed to 50 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Even though there was consistent economic convenience in the telemedicine group, quality of life did not improve in those receiving virtual house calls. Conversely, a study conducted by Durner et al [ 38 ] found, in a group of 50 PD patients provided with a 24/7 live stream telemedicine home treatment service, that, after one year, there was a significant improvement in Parkinson’s Disease Questionnaire 39 (PDQ39) scores, but not in UPDRS, MMSE, or Hoehn & Yahr (H&Y) scores.…”
Section: Telemonitoring In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Even though there was consistent economic convenience in the telemedicine group, quality of life did not improve in those receiving virtual house calls. Conversely, a study conducted by Durner et al [ 38 ] found, in a group of 50 PD patients provided with a 24/7 live stream telemedicine home treatment service, that, after one year, there was a significant improvement in Parkinson’s Disease Questionnaire 39 (PDQ39) scores, but not in UPDRS, MMSE, or Hoehn & Yahr (H&Y) scores.…”
Section: Telemonitoring In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Durante o período do estudo de um ano, 264 chamadas foram realizadas, sendo que este estudo demonstrou que um apoio 24 horas, sete dias por semana era possível, com resultados compatíveis com uma melhor qualidade de vida dos doentes e um grande interesse por parte dos mesmos em prolongar o apoio para além do período do estudo de um ano. 44 Cada vez mais projetos de telemedicina e cuidados continuados com ferramentas de comunicação estão a integrar doentes com doenças do movimento, em diferentes países, e verifica-se que têm revelado bons resultados de acessibilidade e satisfação quer dos doentes quer dos profissionais de saúde. 45…”
Section: Doenças Do Movimentounclassified
“…This is absolutely necessary in case of treating patients who have an emergency situation and need medical attention rapidly. Delays in such cases can be highly dangerous [17]. Therefore, this study has explored the reasons of delays and has proposed measures that can cut down these delays and can improve the live video streaming.…”
Section: A Live Video Streamingmentioning
confidence: 99%